Effectiveness of National Mathematics Program on the Numeracy Skills of Intermediate Pupils - Parra, Roma Guada (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the effectiveness of the National Mathematics Program on the numeracy skills of intermediate pupils in Aldea Elementary School, Tanay District, Schools Division Office of Rizal during School Year 2025–2026. Utilizing an experimental single-group pretest-posttest design, the respondents were 70 intermediate pupils identified as non-numerates. Data were gathered through validated pretest and posttest instruments to measure numeracy skills before and after exposure to the program. Respondents were described in terms of age, sex, sibling position, family size, parents’ educational attainment, parents’ occupation, monthly family income, and grade level. Findings revealed that most respondents were 10–12 years old, male, middle or youngest children, and came from families with 2–5 siblings and average income. Most parents were high school graduates and employed as skilled workers. Results of the pretest indicated that pupils had low numeracy proficiency, while posttest results showed improvement to a higher but still developing proficiency level. Statistical analysis revealed a significant difference between pretest and posttest scores, indicating that the National Mathematics Program is effective in improving numeracy skills. However, no significant differences were found in posttest scores when grouped according to age, sex, sibling position, family size, monthly income, parents’ educational attainment, and parents’ occupation. Only grade level showed a significant difference in numeracy performance. The study concludes that the National Mathematics Program is effective in enhancing numeracy skills among intermediate pupils, while grade level is a determining factor of performance. It is recommended that teachers employ varied and engaging mathematics interventions, pupils be exposed to enriched learning activities, and that a proposed action plan be implemented. Further studies using a two-group experimental design are recommended. The findings contribute to evidence-based mathematics instruction in basic education contexts program implementation.